Clinical significance and biological function of WD repeat domain 54 as an oncogene in colorectal cancer. Issue 7 (11th December 2018) - Yuan, Yuncang; Qi, Guoxiang; Shen, Hao; Guo, Aizhen; Cao, Fuao; Zhu, Yan; Xiao, Chunjie; Chang, Wenjun; Zheng, Shangyong
Abstract : In recent years, protein‐protein interactions have become an attractive candidate for identifying biomarkers and drug targets for various diseases. However, WD40 repeat (WDR) domain proteins, some of the most abundant mediators of protein interactions, are largely unexplored. In our study, 57 of 361 known WDR proteins were identified as hub nodes, and a hub (WDR54) with elevated mRNA in colorectal cancer (CRC) was selected for further study. Immunohistochemistry of specimens from 945 patients confirmed the elevated expression of WDR54 in CRC, and we found that patients with WDR54‐high tumors typically had a shorter disease‐specific survival (DSS) than those with WDR54‐low tumors, especially for the subgroup without well‐differentiated tumors. Multivariate analysis showed that WDR54‐high tumors were an independent risk factor for DSS, with a hazard ratio of 2.981 (95% confidence interval, 1.425–6.234; p = 0.004). Knockdown of WDR54 significantly inhibited the growth and aggressiveness of CRC cells and reduced tumor growth in a xenograft model. Each WDR54 isoform (a, b, and c) was found to reverse the inhibitory effect of WDR54 knockdown; however, only isoform c, which exhibited the highest expression, was increased in CRC cells. Sensitization of WDR54 knockdown to an SHP2 inhibitor was consistently found in CRC cells, and the underlying mechanism involved their common function in regulating AKT and ERK signaling. In conclusion, the present study is the first to investigate the significance of WDR54 in cancer and to conclude that WDR54 serves as an oncogene in CRC and may be a potential prognostic marker and therapeutic target. Abstract : What's new? WD40 repeat (WDR) domain proteins have become attractive therapeutic targets due to their role as mediators of molecule recognition. Here, WDR54 was found to be elevated and associated with prognosis in patients with colorectal cancer (CRC). Functional assays showed that WDR54 facilitates the aggressiveness of CRC cells and promotes tumor growth in mice. Knockdown of WDR54 sensitizes CRC cells to the proliferation‐inhibitory effect of SHP2 inhibitor, an effect involving their common function in regulating AKT and ERK signaling. This first evidence of WDR54 acting as an oncogene highlights WDR54 as a promising therapeutic target and biomarker for CRC.